MINDSET POSITIF MELALUI HUSNUZHON SEBAGAI SELF-HEALING PADA MAHASISWA - Fania, Fania Tri Cahya; Kholil, Kholil Lur Rochman (JIEGC Journal of Islamic Education Guidance and Counselling, 2025)
Self healing or the process of personal recovery plays a crucial role in addressing emotional and mental disturbances. One key factor that supports the success of self healing is the development of a positive mindset. Husnuzhon, which refers to positive thinking toward God, oneself, and others, is a potential approach to fostering such a mindset. This study employs a qualitative phenomenological approach to explore students’ experiences in applying husnuzhon to manage negative emotions and enhance psychological well being. In depth interviews with five informants reveal that husnuzhon contributes to reducing anxiety, strengthening mental resilience, and fostering social relationships. Beyond helping students cope with academic pressure, the practice of husnuzhon also promotes a social environment conducive to personal development. These findings highlight husnuzhon as an effective strategy for improving students' mental health and suggest further research opportunities in the field of educational psychology.